Development of a material handling process and layout for the P356 mirror assembly at Schefenacker SVSA : focus on lean thinking, work environment and quality technology management - Lund, Karin; Ullnert, Anna Maria (2007)
Schefenacker Vision System Australia Pty Ltd (SVSA) is one of 30 companies in the Schefenacker International group, which is the leader in rear vision mirror manufacturer with a 30 percent market share of the world market. SVSA in Adelaide employs over 600 people and the turnover for 2005 was 178 MAUD. This thesis project came about since Schefenacker in Adelaide was going to produce the rear vision mirror for the new Ford Super Duty Truck 2008, with code name P356. Schefenacker desired an optimal material handling process for this complex P356 production. This resulted in cooperation with the University of South Australia and Luleå University of Technology in Sweden and this master thesis project arose. Focus has been put on what could be done in a near future since it felt important to have recommendations that could be put into practice within the close proximity of launch and production. Great importance has been on integrating the employees’ opinions into the development and result of this process. A project cycle method was developed to carry out this thesis work, since it was necessary with a primary method which could manage a constant flow of new information. The model was developed with inspiration from the Deming wheel: plan, do, act and learn, together with Ranhagen’s spiral model: a process should precede several laps before finish. The philosophy Lean thinking has played an important roll throughout the process. Qualitative facts are the base of this project. The information was gathered through literature studies, a questionnaire, observations and interviews with concerned workforce. The survey questionnaire was carried out in the assembly area of the P356 mirror’s predecessor P131. The result from the P131 study has been working as a foundation during the entire project. The authors have been guided for comprehension about which areas improvements would be desirable. The result is also presented in an individual report, consisting of recommendations on how a more efficient production and a better ...